1988
DOI: 10.1007/bf00402877
|View full text |Cite
|
Sign up to set email alerts
|

Cell-lineage patterns in the shoot apical meristem of the germinating maize embryo

Abstract: A fate map for the shoot apical meristem of Zea mays L. at the time of germination was constructed by examining somatic sectors (clones) induced by γ-rays. The shoot apical meristem produced stem, leaves, and reproductive structures above leaf 6 after germination and the analysis here concerns their formation. On 160 adult plants which had produced 17 or 18 leaves, 277 anthocyanin-deficient sectors were scored for size and position. Sectors found on the ear shoot or in the tassel most often extended into the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
2

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(60 citation statements)
references
References 14 publications
3
53
0
2
Order By: Relevance
“…Historically, the concept of monoplex apices has been linked to the notion of a slowly dividing persistent apical cell (Newman, 1965). By contrast, complex meristems of seed plants have a small number of impermanent apical initials in each layer (Bossinger et al, 1992;Dulieu, 1969;Furner and Pumfrey, 1992;Irish and Sussex, 1992;Jegla and Sussex, 1989;Korn, 2001;McDaniel and Poethig, 1988). Our data clearly show that apical initials in the S. kraussiana apex are impermanent and thus it is reasonable to propose that mechanisms that regulate initial cell activity may be conserved in vascular plants.…”
Section: S Kraussiana Shoot Development In the Context Of Land Plantmentioning
confidence: 67%
“…Historically, the concept of monoplex apices has been linked to the notion of a slowly dividing persistent apical cell (Newman, 1965). By contrast, complex meristems of seed plants have a small number of impermanent apical initials in each layer (Bossinger et al, 1992;Dulieu, 1969;Furner and Pumfrey, 1992;Irish and Sussex, 1992;Jegla and Sussex, 1989;Korn, 2001;McDaniel and Poethig, 1988). Our data clearly show that apical initials in the S. kraussiana apex are impermanent and thus it is reasonable to propose that mechanisms that regulate initial cell activity may be conserved in vascular plants.…”
Section: S Kraussiana Shoot Development In the Context Of Land Plantmentioning
confidence: 67%
“…Within the meristem, founder cells for the incipient leaf primordium are recruited in concert with those of the subtending internode and its associated axillary meristem (Sharman, 1942;McDaniel and Poethig, 1988). Together, these vegetative organs comprise a repeating unit of the shoot called a phytomer (Galinat, 1959), and the developmental interval of iterative, phytomer initiation is called a plastochron (Lamoreaux et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…The primary origin of all above-ground tissues of a plant is a dome-like structure named the shoot apical meristem (SAM). These cell-fate analyses have demonstrated that stem cells within the SAM do not have predetermined fates but give rise to organs in a probabilistic way based on their location within this stem-cell niche (20)(21)(22)(23). In Arabidopsis, it is estimated that two to four genetically effective cells (GEC) in the dry seed are the progenitors of late rosettes as well as flowers (20,21,24).…”
mentioning
confidence: 99%